2008
DOI: 10.1074/jbc.m705424200
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Syndecan-1 and Syndecan-2 in Polyethyleneimine-mediated Gene Delivery

Abstract: Polyethyleneimines (PEIs) are efficient non-viral vectors for gene transfer. Heparan sulfate proteoglycans have been proposed to be the cell-surface receptors for PEI⅐DNA complexes (polyplexes). Here, we investigated if syndecan-1 (SDC1) and syndecan-2 (SDC2) are involved in PEI-mediated transfection. Following addition of polyplexes to HEK293 cells, green fluorescent protein-tagged SDCs rapidly formed clusters with PEI that were dependent of lipid raft integrity. However, although SDC1 overexpression slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 52 publications
(49 reference statements)
2
48
1
Order By: Relevance
“…Because of the diverse stainings of SDC4 in the midbody region the distribution of the phosphorylated and non-phosphorylated forms was studied by using green fluorescent protein (GFP)-tagged mutants. The plausible C-terminal fusion of GFP did not provide adequate results in our tests contrary to the published data [28], thus GFP was inserted into the juxtamembrane region of the extracellular domain to avoid the interference with the natural interacting partners of the cytoplasmic domain (Fig. 3a).…”
Section: Resultscontrasting
confidence: 49%
“…Because of the diverse stainings of SDC4 in the midbody region the distribution of the phosphorylated and non-phosphorylated forms was studied by using green fluorescent protein (GFP)-tagged mutants. The plausible C-terminal fusion of GFP did not provide adequate results in our tests contrary to the published data [28], thus GFP was inserted into the juxtamembrane region of the extracellular domain to avoid the interference with the natural interacting partners of the cytoplasmic domain (Fig. 3a).…”
Section: Resultscontrasting
confidence: 49%
“…In mammals, syndecans and glypicans constitute the predominant cell surface HSPGs (5,20). Recently, it has been shown that PEI-DNA complexes bind to syndecans 1 and 2, inducing clustering of these syndecans as an initial step of internalization (42). Depending on the type of syndecan, endocytosis of PEI-DNA complexes follows different kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…6). PEI is reported to have GAG-binding property, and utilized as an HS proteoglycan-mediated DNA transfection agent 15) and a GAG stain for histology. 16) The heparin-inhibiting property of compound 1 was similar to that of PEI (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We thus compared the heparin-neutralizing activity of 1 with that of PEI, which is a polyamine known to interact with heparin/HS proteoglycans, 15,16) by the collagen fibril formation assay (Fig. 7).…”
Section: Principle and Validation Of The Assaymentioning
confidence: 99%